Impact of global supply chain complexity on the individual performance of companies - Grondys Katarzyna; Kot Michał (Engineering Management in Production and Services, 2025)
Cooperation is a key element in building business relationships, particularly when these relationships are complex and implemented on an international scale. The process of globalisation has facilitated the creation of complex networks and the expansion into new markets. However, globalisation has also introduced vulnerabilities due to global crises that disrupt supply chains. In this context, this paper examines the role of global supply chain complexity, specifically focusing on the number of global partners and its impact on the performance outcomes of individual supply chain actors. A multivariate analysis of variance (MANOVA) was employed to test the significance of differences between the studied groups in the independent sample. This approach allows for the examination of how variations in the number of global partners influence multiple performance indicators within the supply chain context. The analysis revealed that a greater number of global partners positively affects several key performance outcomes for companies. Specifically, improvements were observed in lead time, overall supply chain efficiency, inventory and warehouse management, company revenue, and market share. These findings highlight the continued benefits of globalisation despite concerns about its associated risks. This study contributes to the ongoing debate about the advantages and risks of global supply chain complexity. It provides empirical evidence that, while globalisation introduces risks such as instability and reduced resilience, the benefits associated with a greater number of global partners remain significant. This research enhances the understanding of how global connectivity impacts supply chain performance and strategic decision-making for international businesses. The findings suggest that businesses should carefully assess the balance between expanding global networks and managing potential disruptions. Firms can capitalise on the advantages of global partnerships by enhancing key performance outcomes while simultaneously developing strategies to mitigate risks associated with instability. Furthermore, discussions surrounding the regionalisation and shortening of supply chains should consider how strategic global partnerships can complement efforts to build more resilient supply chains.